Biological Aspects of Mackerel Scad (Decapterus macarellus) in the Waters of Ambon Island - Polnaya, Daniela M.; Natan, Yuliana; Pattikawa, Jesaya A. (Agrikan Jurnal Agribisnis Perikanan, 2025)
This study aims to analyze the length-weight relationship, growth pattern and gonad maturity level of the population. Data were collected at the Erie Village Fish Landing Site (PPI), Nusaniwe District, Ambon City, during the period August 2024-January 2025. Samples of mackerel scad obtained were measured for body length and body weight, then analyzed using linear regression and multiple analysis methods to examine fish length-weight relationships and growth patterns, as well as making visual observations of gonad samples with reference to the standard gonad maturity scale to determine the level of gonad maturity of the mackerel scad obtained. The results showed that the coefficient value (b) in the study period ranged from 2.8296-3.2560 with isometric growth pattern (b=3) in January and March, August, September, October and December with positive allometric pattern (b>3) and negative allometric pattern (b<3) in November, February and April. In addition, the distribution of TKG mackerel scad with maturity levels III and IV was found in almost every month of the study. Based on these results, it can be concluded that mackerel scad from the studied population experienced balanced growth in length and body weight in almost every month of capture and proved that mackerel scad spawns throughout the year with the peak spawning season in September-January. This condition needs to be maintained so that the capture and utilization process is in line with the fisheries management strategy to ensure the preservation of a balanced stock of mackerel scad in the water area.